Responses of Red Rice Paddy under Low Nutrient Supply in Type B Tidal Swamp - Asmawati Asmawati; Laili Nisfuriah; Marlina; Joni Rhompas; Dali; Rastuti Kalasari; Ida Aryani; Neni Marlina; Gamal Abdul Nasser; Rosmiah (Biological Environment and Pollution, 2022)
Low soil fertility can constrain the paddy red rice yield. One of the efforts to increase paddy red rice production at the Tidal swamp area is using iron toxicity tolerant varieties. The objectives of this research were (i) to evaluate the agronomic responses of red paddy rice to low nutrient supply to determine the sensitive character and (ii) to identify the tolerant and nutrient-efficient variety under low nutrient supply in a tidal swamp area. The experiment was conducted at Tidal Swamp Area Type B, Telang Sari Village, Banyuasin District, South Sumatra Province. The experimental design was Split Plot with five replications. Nutrient supply was the main plot, and the Varieties (Inpara 7; Inpago 7, Aek Sibundong, and Telang Sari) were the subplot. The nutrient supply treatments were H1: standard fertilizer rate and H2: low nutrient supply, which is 30% of the standard rate. The results showed that Inpago 7 and Inpara 7 were potential varieties at low nutrient supply. The sensitive characteristics of the varieties evaluated were chlorophyll content, number of tillers, grain weight, and percentage of empty grain for growth and production characters.